Temperate and Subtropical Fruit Production. Second Edition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by D I Jackson (Department of Plant Science, Lincoln University, New Zealand) and N E Looney (Pomology and Viticulture Section, Agriculture and Agri-Food Canada, Canada). CABI. 1999. 336 pp.ISBN 0851992714.£30.00 $55.00 Euro 52.90(See...